Strength of multilayered plates with impact damage - V.I. Mitryaykin; O.N. Bezzametnov (Учёные записки Казанского университета: Серия Физико-математические науки)
This article solves one of the central problems of how impact damage affects the strength of polymer composite materials (PCM). Impact damage on sandwich materials varies in the resulting shape and size, thus hampering the numerical assessment of their stress-strain state because these damage characteristics are difficult to predict. Here, we introduced an experimental technique to determine the PCM strength and modeled the impact damage on rectangular plates to illustrate the conclusions drawn. The critical compressive load and stress of the undamaged plates were obtained by the finite element method. The experimental correction function was deduced to evaluate the effect of the damage area and impact energy on the residual strength. Vertical impact testing of the PCM samples was performed. Following the impact on the plate, the depth of the dents and the damage area were measured using the pulse-echo ultrasonic technique. The failure behavior was analyzed layer by layer for individual samples with the help of X-ray computed tomography. For a number of PCM samples, a relationship between the damage size and the impact energy was established. Compression testing of the damaged plates was carried out. The critical buckling loads and the functions of a decrease in the load-bearing capacity of the plates depending on the impact energy value were calculated.